THE PRAGMATICS OF SWEARING: HOW IT CONTEXTUALLY COUNTS - Jumanto Jumanto; Haryati Sulistyorini (Universitas Muhammadiyah Semarang, 2019)
This paper explores swearing utterances in English language use, the hearers referred to, and the functions the utterances imply. Accounts on the issue are taken from the English-language-affiliated Websites in the Internet. This research is a literature review with interpretative techniques and employs a coding analysis with three proposed premises. As the findings, swearing utterances belong to informal English with notorious, casual, heteregeneous, inconsistent, irregular, and speaker-dependent aspects. Swearing utterances have elaborated literal meaning and creative meaning to various contexts, which are personal and private. Swearing utterances to others are rude, offensive, profane, or obscene, as expressions of anger; however, when adjusted to the context of hearer, the meanings or functions vary. Swearing utterances to others create rude and offensive situations. However, swearing utterances to close people through jokes and possitive connotations may instill solidarity or confirm camaraderie. Swearing utterances concerning internal expressions or expletives function to intensify the messages.